How did New Zealanders decide to get vaccinated against COVID-19? Developing a novel comprehensive model of vaccination intention - Rahmani D; Fletcher P; Hess AC; Croucher S (Taylor and Francis Group on behalf of the National Communication Association, 2024)
This research introduces and validates the Comprehensive Model of Vaccination Intention (CMVI) to offer a holistic understanding of COVID-19 vaccination uptake in New Zealand. The CMVI excels by presenting a highly explanatory model, incorporating trust in the government's vaccination policy along with and a spectrum of social, cognitive, contextual, and affective variables from theories of Interpersonal Behavior, Planned Behavior, and Health Belief Model. A nationally representative sample of 993 participants was analyzed using confirmatory factor analysis and structural equation modeling. The findings underscore the positive impact of subjective norms and societal perceptions of vaccination, attitude toward vaccination, trust in government, and vaccination habits on COVID-19 vaccination intention. This study highlights the importance of normalizing vaccination to boost intention and shows how emotions shape attitudes. It also finds that better vaccine accessibility and trust in the government lower perceived costs and raise perceived benefits, improving overall attitude and strengthening vaccination intention.
Keywords: COVID-19; vaccine intention; theory of interpersonal behavior; theory of planned behavior; health belief model; New Zealand